First investigation of the presence of SPATE genes in Shigella species isolated from children with diarrhea infection in Ahvaz, southwest Iran - Moosavian, Mojtaba (Infect Drug Resist, 2019)
Background: SPATE (serine protease autotransporters of enterobacteriaceae) genes are considered as a group of the main virulence factors of Shigella species This study aimed to investigate for the first time the distribution of SPATE genes among Shigella spp. isolated from children with diarrhea infection in Ahvaz, Iran. Methodology: In this study, a total of 74 Shigella isolates were collected between August 2016 and June 2017 from feces of children with diarrhea and identified by biochemical and molecular methods for Shigella species. The frequency distribution of the SPATE genes, including pic, pet, sat, sigA and sepA, was evaluated using PCR. The genetic relationship of all isolates was evaluated by enterobacterial repetitive intergenic consensus-PCR. Results: The most common species of Shigella was S. flexneri, followed by S. sonnei and S. boydii. In total, 95.94% of Shigella isolates had at least one of the SPATE genes. The presence of pic, pet, sat, sigA and sepA genes was confirmed among 35.13%, 27%, 47.29%, 58.1% and 39.18% of Shigella isolates, respectively. Of these SPATE genes, the sat and sigA genes were recognized as the most common autotransporters among S. flexneri and S. sonnei isolates, respectively. Also, either S. flexneri or S. sonnei isolates belonging to a same clone type had similar SPATE genes profile. Conclusion: Our results revealed that the high distribution of SPATE genes among Shigella isolates in our region. Hence, this study highlights a need for epidemiological programs to monitor the distribution of SPATE genes locally for prevention from further dissemination of the Shigella isolates harboring them.